Varsities retain research status - The Sun, (2010)
Universiti Malaya,Universiti Kebangsaan Malaysia,Universiti Sains Malaysia and Universiti Putra Malaysia have retained their status as research universities for another three years beginning this year,Higher Education Minister Datuk Seri Mohamed Khaled Nordin said yesterday.He said the decision to retain their resarch university status was based on the audit report for the year 2007 to 2009.